2016
DOI: 10.1177/0194599816633654
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Audiologic Outcomes in Endoscopic Stapes Surgery across 4 Institutions

Abstract: The present multicentered study of endoscopic stapes surgery demonstrates similar audiometric and postoperative outcomes previously published in the literature, with a median postoperative air-bone gap of 9.0 dB HL. Future prospective endoscopic stapes surgery studies, addressing the need for scutum removal, postoperative taste changes, and pain scores, are merited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 19 publications
1
31
0
5
Order By: Relevance
“…Of the 160 articles identified in the primary search strategy, 135 were excluded due to non‐English language (n = 5), individuals under 18 years (n = 1), and studies completely unrelated to endoscopic stapes surgery (n = 140). After the above screening process, the total number of articles qualified for review was 14 (Table ) . Four of these were level III, and 10 were level IV evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 160 articles identified in the primary search strategy, 135 were excluded due to non‐English language (n = 5), individuals under 18 years (n = 1), and studies completely unrelated to endoscopic stapes surgery (n = 140). After the above screening process, the total number of articles qualified for review was 14 (Table ) . Four of these were level III, and 10 were level IV evidence.…”
Section: Resultsmentioning
confidence: 99%
“…All patients had preoperative and at least 6 weeks of postoperative audiologic data. Audiometric testing and calculations were conducted as previously described . Audiometric data herein are presented according to the 1995 American Academy of Otolaryngology–Head and Neck Surgery consensus guidelines .…”
Section: Methodsmentioning
confidence: 99%
“…Although prior studies have demonstrated similar audiologic and surgical outcomes between endoscopic and microscopic approaches for primary stapes surgery, endoscopic outcomes for revision stapes surgery have not been previously reported. This case series describes the presentation, clinical course, and outcomes of six patients who underwent endoscopic revision stapes surgery.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, there has been a number of publications comparing the two modalities and only one review, but no meta‐analysis that attempted to collect all evidence on the field . Therefore, we decided to systematically review the literature for studies that compared endoscopic with microscopic stapes surgery to perform a meta‐analysis to test our hypothesis: endoscopy performs better than microscopy.…”
Section: Introductionmentioning
confidence: 99%